The Right to Know: A Revised Standard for Reporting Incidental Findings - Schaefer, G. Owen (The Hastings Center report, 2018)
During the course of biomedical research, researchers sometimes obtain information on participants that is outside the aim of the study but may nonetheless be relevant to the participants. These incidental findings, as they are known, have been the focus of a substantial amount of discussion in the bioethics literature, and a consensus has begun to emerge about what researchers should do in light of the possibility of incidental findings. A consensus, however, is not necessarily correct. In this article, we address the common view that reporting of incidental findings should be based primarily on the possibility of medical benefit, factoring in the findings’ validity, clinical actionability, and significance to health or reproduction. While such medical beneficence should not be discarded, the need to give proper attention to participants’ autonomy, privacy, and interests (especially considering discussion of participants’ right not to know) suggests an alternative standard for when to report incidental findings: even if they are of no direct medical benefit, incidental findings should be reported based on the extent to which the participant can be expected to comprehend the information. We will offer a preliminary defense of this alternative as best respecting participants’ autonomy and privacy and promoting their interests. However, we acknowledge that the standard would face significant practical barriers, and these barriers lead us to propose a metaconsent addendum that would allow subjects to essentially waive the comprehension standard when resource or other constraints make meeting it impracticable.